"Just Describing is Not Enough": Policy Learning, Transfer, and the Limits of Best Practices. Issue 2 (15th March 2018) - Mattocks, Kate
ABSTRACT: Despite widespread use in the cultural field, best practices remain theoretically and empirically under-researched. The aim of this article is to achieve better understanding of their use and effectiveness in policy learning and transfer, using a case study of a cross-national policy coordination process in the European Union, the Open Method of Coordination. Using empirical data from interview and participant observation material, the article highlights several fundamental challenges of best practices, such as issues of contextualization, representativeness, and critical analysis. It finishes by offering six critical reflection questions on the use of best practices.